The Influence of Student Team Achievement Division (STAD) Cooperative Learning Model on Third Graders’ Civic Education Learning Outcomes - Nimatul Maola; Khavisa Pranata (Program Studi Pendidikan Guru Sekolah Dasar, FKIP, Universitas Riau, 2022)
This study discussed about the influence of student team achievement division (STAD) learning model on third graders’ civic education learning outcomes. This research used quantitative research method, and the participants were 30 students. The data analysis begins by conducting validity and normality test, and it is continued by implementing STAD learning model in the classroom. Students’ civic education learning outcomes reached the score at 62.40 before the implementation, and it increased into 83.73 after giving the instruction learning using STAD learning model. It implies that STAD learning model have positive affects towards third graders’ civic education learning model.